PEREMPUAN KURIR DALAM PERDAGANGAN GELAP NARKOBA (SEBUAH REALITAS KORBAN KEKERASAN BERLAPIS) - Ayu Anastasia (Jurnal Kriminologi Indonesia, 2012)
This research is aimed to see the social context of women which is involved in drug trafficking that is seen from criminology and gender overview. This study also describes the experience of violence by drug couriers women and their response to the violence. In analyzing the data, the researcher uses feminist perspective which have contribution to defend rights and justice for women. This research method appertain into field research with indepth interviews. While the research approach is qualitative which use criminology feminist perspective. Researcher have conducted interviews 2 women as the core subjects. The result find that they get violent in layers like an unbroken vicious circle and continuity. It closely related between the violence they receive with the beginning of their implication in crimes, when they do crimes and when they are in the process of criminal justice.